Open and Distance Education Policies and Practices in Prisons in Portugal - Angélica Monteiro; Carlinda Leite; Ana Machado; Rita Barros (Journal of Learning for Development, 2025)
This study explores the implications of open and distance learning environments for promoting educational practices suitable for inmates. The research questions focus on the regulatory, technological and humanistic perspectives of digital technology in prison, addressing the relationship between adult education policies and practices, the experience of distance learning in the prison context, and the implications of these policies in the field. Data collected from documentary analysis and four interviews with trainers and administrative staff highlight the need for comprehensive and inclusive policies and strategies to enhance digital inclusion and lifelong learning opportunities for these populations. Recommendations include expanding the conditions for research, fulfilling adult education rights in prison, increasing digital literacy and competencies, ensuring safe internet use, and fostering a supportive, open and distance learning environment within the prison system.